2022
DOI: 10.1002/14651858.cd015112.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Workplace interventions to reduce the risk of SARS-CoV-2 infection outside of healthcare settings

Abstract: Workplace interventions to reduce the risk of SARS-CoV-2 infection outside of healthcare settings (Protocol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Consistent with these findings, we found that Hong Kong people with higher socioeconomic status reported more perceived benefits, whereas those with lower socioeconomic status reported more perceived harms from the COVID-19 outbreak ( 21 ). Our search of PubMed using the keywords “benefits” and “harms” and “socioeconomic” and “COVID-19” up to 5 June 2022 yielded seven reports (excluding our own) that investigated both potential benefits and harms of COVID-19 ( 6 , 22 27 ). However, these reports were based largely on qualitative data or casual observations; none directly compared both perceived benefits and harms and their socioeconomic disparities between early and later waves of outbreak amid the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, we found that Hong Kong people with higher socioeconomic status reported more perceived benefits, whereas those with lower socioeconomic status reported more perceived harms from the COVID-19 outbreak ( 21 ). Our search of PubMed using the keywords “benefits” and “harms” and “socioeconomic” and “COVID-19” up to 5 June 2022 yielded seven reports (excluding our own) that investigated both potential benefits and harms of COVID-19 ( 6 , 22 27 ). However, these reports were based largely on qualitative data or casual observations; none directly compared both perceived benefits and harms and their socioeconomic disparities between early and later waves of outbreak amid the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The reviews looking at active surveillance measures [24, 25, 27, 33, 108] found that: routine testing of residents and staff independent of symptoms may reduce the number of infections and hospitalizations in long‐term care facilities. Routine testing may also reduce the number of deaths among residents, but it is uncertain whether it reduces deaths among staff or whether it increases or decreases the probability of outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“… Test‐based attendance policy in schools may result in little to no difference in absence rates compared with standard 10‐day self‐isolation among school and college staff (one high confidence review) [25]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations